2015
DOI: 10.1155/2015/780197
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Residue Scale: An Easy-to-Use and Reliable Videofluoroscopic Analysis Tool to Score Bolus Residue in Patients with Dysphagia

Abstract: Background. We aimed to validate an easy-to-use videofluoroscopic analysis tool, the bolus residue scale (BRS), for detection and classification of pharyngeal retention in the valleculae, piriform sinuses, and/or the posterior pharyngeal wall. Methods. 50 randomly selected videofluoroscopic images of 10 mL swallows (recorded in 18 dysphagia patients and 8 controls) were analyzed by 4 experts and 6 nonexpert observers. A score from 1 to 6 was assigned according to the number of structures affected by residue. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…These investigators studied children utilizing high resolution esophageal pressure topography, impedance, and videofluoroscopy methods 3,4953 . Notable works that may translate to the neonatal population include: 1) assessment of oropharyngeal dysphagia and aspiration utilizing pressure-flow analysis, a method to assess swallowing physiology by detecting motor function, bolus flow and transit, and correlation with symptoms, 5458 and 2) development a bolus residue scale to detect pharyngeal retention 59 .…”
Section: ) Pathophysiology Of Aerodigestive Systemsmentioning
confidence: 99%
“…These investigators studied children utilizing high resolution esophageal pressure topography, impedance, and videofluoroscopy methods 3,4953 . Notable works that may translate to the neonatal population include: 1) assessment of oropharyngeal dysphagia and aspiration utilizing pressure-flow analysis, a method to assess swallowing physiology by detecting motor function, bolus flow and transit, and correlation with symptoms, 5458 and 2) development a bolus residue scale to detect pharyngeal retention 59 .…”
Section: ) Pathophysiology Of Aerodigestive Systemsmentioning
confidence: 99%
“…However, Malandraki et al [37] used a 3-point residue scoring system [51] to measure the volume of residue and examined the relationship between pitch glide and pharyngeal residue and concluded that maximum F 0 of sound /a/ was associated with residue in patients with different aetiologies of dysphagia. In the current study the Bolus Residue Scale [45] was used in order to detect and classify residue in the valleculae, piriform sinuses and/or posterior wall of the pharynx. It is important to highlight the fact that these three studies used three different scales and each one was focused on different diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Penetration-Aspiration Scale was used to rate aspiration on 5 mL, 10 mL and the sip of liquids from 1 (material does not enter the airway) to 8 (material enters the airway; passes below the vocal folds, no effort made to eject) [44]. Pharyngeal residue and hyolaryngeal excursion were rated using Bolus Residue Scale and the hyolaryngeal excursion component of the MBSImP, respectively [43, 45]. Residue was rated on a scale from 1 (no residue) to 6 (residue in valleculae and posterior pharyngeal wall and piriform sinus) [45].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolus retention patterns are associated with specific physiologic impairments. [72][73][74][75] In the stroke population, bolus retention may present in a variety of patterns. One pattern might represent unilateral weakness, in which case secretions, food, or liquid collect in the pharyngeal recesses on the side of weakness.…”
Section: Swallow Events: Bolus Retentionmentioning
confidence: 99%